Stock prices, exchange rates and causality in Malaysia : a note - Azman Saini, W.N.W.; Habibullah, M.S.; Dayang Affizzah, Awang Marikan; Law, Siong Hook (Economic Division, 2006)
This article contributes to the debate on stock prices and exchange rates in Malaysia. It examines causal relations using a new Granger non-causality test proposed by Toda and Yamamoto (Journal of Econometrics, 66, 225-50, 1995). Among the findings of interest, there is a feedback interaction between exchange rates and stock prices for the pre-crisis period. The results also reveal that exchange rates lead stock prices for the crisis period. In a financially liberalized environment, exchange rates stability is important for stock market well-being.